Management of patients with acromegaly in clinical practice in the gulf countries: a Delphi consensus survey - Almalki, Mussa H.; Elhadd, Tarik; AlDahmani, Khaled M.; Ekhzaimy, Aishah; Alqanaei, Abdullah; Frookh, Hasan; Alyamani, Arwa; Hakami, Osamah; Dabbous, Zeinab; Rohani, Zaina; Almistehi, Wael; Aljumah, Hazem; et al. (Frontiers in Endocrinology, 2025)
BackgroundAcromegaly management practices in the Gulf region lack standardized guidelines, leading to variability in care. This study aimed to establish evidence-based regional consensus recommendations to address clinical challenges and align management with local healthcare resources.MethodsA three-round Delphi consensus survey was conducted among 15 endocrinology experts from six Gulf countries. Forty-six statements across six domains—primary treatment, pre-surgery treatment with somatostatin analogs (SSAs), second-line therapy, radiotherapy, post-surgery follow-up, and long-term management—were evaluated. Consensus was predefined as ≥66.8% agreement.ResultsStrong consensus was achieved on surgical resection as first-line therapy for eligible patients (100% agreement), with referrals to multidisciplinary centers emphasized (93.8%). Preoperative SSAs were endorsed to reduce surgical/anesthesia risks in high-risk patients (93.8%). For second-line management, watchful waiting for asymptomatic patients with mildly elevated insulin-like growth factor-1 (IGF-1) (93.8%) and combination therapy (where feasible) were supported. Radiotherapy received unanimous agreement for specific cases. Structured post-surgical follow-up protocols, including biochemical testing timelines and remission criteria, were established. Long-term monitoring emphasized individualized risk assessment.DiscussionThese guidelines provide a regionally tailored framework for acromegaly management, prioritizing surgery as the cornerstone of treatment while integrating adjuvant therapies and follow-up strategies aligned with Gulf healthcare infrastructures. The consensus reflects pragmatic adaptations to resource availability, such as endorsing watchful waiting in specific contexts. While acknowledging limitations such as potential expert bias, these consensus guidelines provide a framework for standardizing acromegaly care across the Gulf countries, with emphasis on surgical intervention as the cornerstone of treatment while recognizing the importance of adjunctive therapies.